Marine aquaculture development and tourism: The case of Cyprus - Stephanou D. (Aquaculture planning in Mediterranean countries, 1999)
The paper deals with the interactions between marine aquaculture and tourism development in the touristic island of Cyprus and the relevant government policy. Tourism is the main industry with significant contribution to the GDP, while mariculture in offshore cages is a new development which is providing good quality fish in increasing quantities to a local market that covers about 60 per cent of its needs in fish and fishery products by imports. The massive growth of the algae Cladophora and its repercussions on the tourist industry played a decisive role in the adoption of offshore cage technology for fattening fish. The present state of marine aquaculture and tourism is described and the latter is discussed and analysed as consumer of aquaculture products and as competitor with mariculture for coastal land and sea areas. Information is given on the public reactions on the perceived environmental impact of fish farms. The government policy aims at safeguarding the development of both activities. Procedures and regulations for the establishment of farms, their environmental impact and the monitoring of their operations are being examined. The role of marine aquaculture as a tourist attraction is examined and the relevant regulations on recreational fishing around the fish farms are stated. The paper concludes that tourism and marine aquaculture interact both positively and negatively on each other and an integrated approach is advisable on coastal zone management. Although tourism development is given priority, the government policy aims at the sustainable development of both activities which could lead to the diversified use of the sea resource on the island.
Workshop of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1998/03/12-14, Tangiers (Morocco)